Machine learning method for the classification of the state of living organisms’ oscillations - Kweku, David; Villalba, Maria I.; Willaert, Ronnie G.; Yantorno, Osvaldo M.; Vela, Maria E.; Panorska, Anna K.; Kasas, Sandor (Frontiers in Bioengineering and Biotechnology, 2024)
The World Health Organization highlights the urgent need to address the global threat posed by antibiotic-resistant bacteria. Efficient and rapid detection of bacterial response to antibiotics and their virulence state is crucial for the effective treatment of bacterial infections. However, current methods for investigating bacterial antibiotic response and metabolic state are time-consuming and lack accuracy. To address these limitations, we propose a novel method for classifying bacterial virulence based on statistical analysis of nanomotion recordings. We demonstrated the method by classifying living Bordetella pertussis bacteria in the virulent or avirulence phase, and dead bacteria, based on their cellular nanomotion signal. Our method offers significant advantages over current approaches, as it is faster and more accurate. Additionally, its versatility allows for the analysis of cellular nanomotion in various applications beyond bacterial virulence classification.